Lipidomic Study of Precursors of Endocannabinoids in Freshwater Bryozoan Pectinatella magnifica - Řezanka, Tomáš; Vítová, Milada; Lukavský, Jaromír; Sigler, Karel (Lipids, 2018)
Freshwater bryozoan Pectinatella magnifica was collected from a sand pit (South Bohemia). The total lipids after extraction from lyophilized bryozoans were analyzed using high-performance liquid chromatography/high-resolution negative tandem electrospray mass spectrometry. A total of 19 lipid classes were identified, including N-acyl-substituted phospholipids, that is, N-acylphosphatidylethanolamine and N-acylphosphatidylserine in their plasmenyl forms. Based on gas chromatography/mass spectrometry of 3-pyridylcarbonyl (picolinyl) esters, a very unusual fatty acid was identified, namely 24:7n-3 (all-cis-3,6,9,12,15,18,21-tetracosaheptaenoic acid). The presence of polyunsaturated fatty acids in individual classes is very specific: arachidonic and eicosapentaenoic acids being predominantly bound as amides in N-acyl phospholipids, that is, diacyl-N-acylphosphatidylethanolamines (NAPtdEtn), plasmenyl-N-acylphosphatidyl ethanolamines (PlsNAPtdEtn), diacyl-N-acylphosphatidylserines (NAPtdSer), and plasmenyl-N-acylphosphatidylserines (PlsNAPtdSer). While 24:6n-3 was identified in the sn-2 position of several phospholipids, 24:7n-3 was identified in only two plasmalogens, that is, PlsNAPtdEtn and PlsNAPtdSer. Thanks to the tandem mass spectrometry, we managed to identify the position of all acyl groups in both diacyl- and also in alkenyl-acyl-(plasmenyl) molecular species of N-acylphospholipids. The identification of the molecular species of N-acyl-substituted phosphatidylethanolamine and phosphatidylserine, including their plasmalogen forms, in the freshwater bryozoan P. magnifica has enabled the identification of endogenous cannabinoid precursors.
Keywords: Chromatography, High Pressure Liquid; sladká voda; tandemová hmotnostní spektrometrie; Liquid chromatography/tandem high-resolution electrospray mass spectrometry; endokanabinoidy; Animals; Endocannabinoids; Pectinatella magnifica; Tandem Mass Spectrometry; Bryozoa; Fresh Water; zvířata; vysokoúčinná kapalinová chromatografie; Freshwater bryozoan; N-acylphosphatidylethanolamines; Lipidomics